2018
DOI: 10.3389/fphar.2018.01366
|View full text |Cite
|
Sign up to set email alerts
|

EGCG Reduces Obesity and White Adipose Tissue Gain Partly Through AMPK Activation in Mice

Abstract: (-)-Epigallocatechin-3-gallate (EGCG), which is the most abundant catechin in green tea, has many potential health benefits, including decreased weight gain and/or adipose tissue weight. Suggested mechanisms for body weight reduction by EGCG include: (1) a decrease in calorie intake and (2) activation of AMPK in liver, skeletal muscle, and white adipose tissue. However, only one study supports the AMPK hypothesis. To determine the role of AMPK in EGCG-induced reduction of body weight, we administrated 50 mg/kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
79
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(106 citation statements)
references
References 26 publications
6
79
0
1
Order By: Relevance
“…EGCG is one of the most abundant and potent polyphenols in green tea. As with other polyphenolic compounds, EGCG has been studied for its antioxidant, anti-inflammatory, and anti-obesity effects [ 135 , 136 , 137 ]. When treated with EGCG for 16 weeks, mice placed on a HFD and 10% fructose solution resisted obesity development and displayed better CNS insulin sensitivity than HFD-fed obese control mice [ 138 ].…”
Section: Role Of Antioxidants/anti-inflammatory Agents In the Cnsmentioning
confidence: 99%
“…EGCG is one of the most abundant and potent polyphenols in green tea. As with other polyphenolic compounds, EGCG has been studied for its antioxidant, anti-inflammatory, and anti-obesity effects [ 135 , 136 , 137 ]. When treated with EGCG for 16 weeks, mice placed on a HFD and 10% fructose solution resisted obesity development and displayed better CNS insulin sensitivity than HFD-fed obese control mice [ 138 ].…”
Section: Role Of Antioxidants/anti-inflammatory Agents In the Cnsmentioning
confidence: 99%
“…Reportedly, the intragastric administration of 100 mg/kg EGCG over the course of 20 weeks resulted in a significant increase in the activation of AMPK in the subcutaneous and epididymal adipose tissue of the mice. This finding is accompanied by a decrease in epididymal adipose tissue weight gain, triglycerides, cholesterol, and low-density lipoprotein cholesterol (LDL-C) levels, as well as an increase in high-density lipoprotein cholesterol and fecal free fatty acids levels, and the mRNA expression of lipolysis and fatty acid oxidation genes in WAT (101). In summary, the authors showed that EGCG alleviates hyperlipidemia in mice through AMPK activation to a certain extent.…”
Section: Epigallocatechin-3-gallatementioning
confidence: 87%
“…In a more recent discovery, Li et al have provided new insights into the mechanisms by which EGCG decreases the susceptibility of male C57BL/6J mice to HFD-induced obesity (101). Reportedly, the intragastric administration of 100 mg/kg EGCG over the course of 20 weeks resulted in a significant increase in the activation of AMPK in the subcutaneous and epididymal adipose tissue of the mice.…”
Section: Epigallocatechin-3-gallatementioning
confidence: 99%
“…37) Gallic acid was also reported to increase glucose uptake in 3T3-L1 cells in an PI3 kinase-dependent manner without AMPK activation, 38) and in this case, it is presumed that AMPK was not activated due to low concentration and insufficient treatment time of gallic acid. In addition to gallic acid, several other polyphenol compounds, including resveratrol, 39) quercetin, 40) curcumin, 41) and catechins, 42) can also activate AMPK and attenuate the effects of metabolic syndrome. AMPK activation occurs due to allosteric activation by AMP accumulation as a result of ATP depletion.…”
Section: Discussionmentioning
confidence: 99%